E-075 Low yield of cerebral angiography in adequately occluded aneurysms after flow diversion. (22nd July 2018) - Chalouhi, N; Patel, P; Atallah, E; Chitale, A; Lang, M; Tjoumakaris, S; Hasan, D; Smith, M; Rosenwasser, R; Jabbour, P
Abstract : Background and purpose: Flow diversion has emerged as a highly effective treatment for intracranial aneurysms. We assess the yield of further angiographic follow-up in aneurysms that have achieved adequate occlusion after treatment with the Pipeline Embolization Device (PED). Methods: This is a single institution, retrospective study. Inclusion criteria were as follows: 1) patients with one or more aneurysms treated with PED, 2) available short term (<12 months) follow-up digital subtraction angiography (DSA), 3) complete (100%) or near-complete (>95%) occlusion on short-term follow-up DSA, and 4) available further angiographic follow-up (DSA, MRA, or CTA). Results: A total of 146 patients were identified. Aneurysm size was 8.4±5.1 mm on average. Mean angiographic follow-up time was 29.7±12.2 months. On short-term follow-up DSA images, 132 (90.4%) had complete aneurysm occlusion and 14 (9.6%) had near-complete occlusion. Four patients (3%) had further DSA follow-up alone, 30 patients (21%) had further DSA and MRA/CTA follow-up, and 112 patients (76%) had further MRA/CTA follow-up alone. On further angiographic follow-up (DSA, MRA, and/or CTA), no patient had a decrease in the degree of aneurysm occlusion (recurrence) or required retreatment. Of the 14 patients with near-complete occlusion on initial DSA images, 7 patients (50%) progressed to complete aneurysm occlusion on further angiographic follow-up. Conclusion: This study did not find any diagnostic yield in repeating cerebral angiography in adequately occluded aneurysms with the PED. We do not recommend repeat angiographic follow-up once aneurysms have achieved complete occlusion with the PED unless clinically warranted. Disclosures: N. Chalouhi: None. P. Patel: None. E. Atallah: None. A. Chitale: None. M. Lang: None. S. Tjoumakaris: None. D. Hasan: None. M. Smith: None. R. Rosenwasser: None. P. Jabbour: None.